Activation of estrogen receptor beta (ERβ) regulates the expression of N-cadherin, E-cadherin and β-catenin in androgen-independent prostate cancer cells. (March 2018) - Silva, Rafael de Souza; Lombardi, Ana Paola G.; de Souza, Deborah Simão; Vicente, Carolina M.; Porto, Catarina S.
Graphical abstract: Highlights: ERβ decreases the expression of N-cadherin and increases β-catenin in the cytoplasm of PC-3 cells. ERβ increases the expression of E-cadherin and β-catenin in the plasma membrane of DU-145 cells. In PNT1A cells, activation of ERβ does not affect the expression of N-cadherin and β-catenin. Differential expression and localization of N-cadherin, E-cadherin and β-catenin is detected in androgen-independent prostate cancer cells. Abstract: The aim of the present study was to investigate the impact of the activation of estrogen receptors on expression and localization of N-cadherin, E-cadherin and non-phosphorylated β-catenin in androgen-independent prostate cancer cells (PC-3 and DU-145) and in human post pubertal prostate epithelial cells (PNT1A). Expression of N-cadherin was detected in PNT1A and PC-3 cells, but not in DU-145 cells. E-cadherin was detected only in DU-145 cells and β-catenin was detected in all cells studied. N-cadherin and β-catenin were located preferentially in the cellular membrane of PNT1A cells and in the cytoplasm of PC-3 cells. E-cadherin and β-catenin were located preferentially in the cellular membrane of DU-145 cells. 17β-estradiol (E2) or the ERα-selective agonist PPT did not affect the content and localization of N-cadherin in PC-3 and PNT1A cells or E-cadherin in DU-145 cells. In PC-3 cells, ERβ-selective agonist DPN decreased the expression of N-cadherin. DPN-induced downregulation of N-cadherin was blocked by pretreatment with the ERβ-selective antagonist (PHTPP), indicating that ERβ1 is the upstream receptor regulating the expression of N-cadherin. In DU-145 cells, the activation of ERβ1 by DPN increased the expression of E-cadherin. Taken together, these results suggest that activation of ERβ1 is required to maintain an epithelial phenotype in PC-3 and DU-145 cells. The activation of ERβ1 also increased the expression of β-catenin in cytoplasm of PC-3 and in the cellular membrane of DU-145 cells. In conclusion, our results indicate differential expression and localization of N-cadherin, E-cadherin and β-catenin in androgen-independent prostate cancer cells. The reduction of N-cadherin content by activation of ERβ, exclusively observed in androgen-independent prostate cancer cells (PC-3), may be related to the activation of signaling pathways, such as the release of β-catenin into the cytoplasm, translocation of β-catenin to the nucleus and activation of gene transcription.